Description of the larvae of Thermonectus alfredi GRIFFINI, 1898 (Coleoptera: Dytiscidae) - Michat, Mariano Cruz (2013)
The three larval instars of Thermonectus alfredi GRIFFINI, 1898 (Coleoptera: Dytiscidae) are described and illustrated for the first time, emphasizing the morphometry and chaetotaxy. In this species, the median process of the prementum is slightly bifid apically, bearing two spine-like setae (LA8), which are diagnostic features of the genus Thermonectus DEJEAN, 1833. The first instar of T. alfredi differs from that of T. succinctus (AUBÉ, 1838) in the number of additional spine-like setae on the dorsal surface of the stipes and on the anterodorsal surface of the prementum, and in the presence of additional anterodistal setae on the metafemur. On the other hand, the third instar of T. alfredi differs from those of T. basillaris (HARRIS, 1829) and T. succinctus in the number of secondary setae on the femur and the metatibia, and from that of T. nigrofasciatus ornaticollis (AUBÉ, 1838) in the length of seta LA8, which is shorter than the median process of the prementum.